ANALYSIS EFFECT OF LEACHATE ON SANDY CLAY SOIL - Aribudiman, I Nyoman; Redana, I Wayan; Diana Harmayani, Kadek; Ciawi, Yenni (International Journal of Engineering and Emerging Technology; Vol 4 No 1 (2019): January - June, 2019)
Soil as a place of establishment of building can be very vulnerable to experiencing changes, especially by the influence of surrounding environment. Leachate has definition of waste water that formed from waste seepage water roomates is Often found in a dumpsite. The difference in the effect of leachate levels on soil characteristics soil changes may results. The aim of the research is to know the effect of leachate on soil characteristic in landfill Temesi, Gianyar. This is at the sampling site Because there is untreated leachate pollutes soil roomates around dumpsite. In testing the soil characteristics in the form of physical properties, mechanical properties, and soil permeability, the sample collected from the landfill leachate Temesi and determined by level variations with a percentage of 0%, 20%, 40%, 60%, 80% and 100% to water added to sandy clay soil with Atterberg limits test to Obtain Data on soil physical properties in the form of liquid limit values, plastic limits, and shrinkage limits. The CD (Consolidated Drained) triaxial tests to Obtain Data on soil mechanical properties in the form of cohesion values (c) and internal friction angle (?). The test was Carried at Soil Mechanics Laboratory of the Faculty of Engineering Udayana University. The result of Atterberg limits test with 0% to 100% leachate Increased by 39.91% to 57.18% for liquid limit, 22.81% to 43.63% for plastic limit, and 34.23% to 50.41% for shrinkage limit with average increase of 8.65% for liquid limit , 18:26% for plastic limit, and 9:45% for shrinkage limit. For the result of CD triaxial tests with 0% to 100% leachate Decreased by 5.6 ° to 12.2 ° internal friction angle (?) and 0. 349 kg/cm 2 to 0249 kg/cm 2 for cohesion values (c) with average decline 10.82% for internal friction angle (?) and 5.73% for cohesion value (c). The permeability value with 0% to 100% leachate Decreased by 0.000163 cm/seconds to 0.000075 cm/seconds with average decline 10.79%.